STUDY OF BIRD DIVERSITY IN THE SRIWIJAYA KINGDOM'S ANCIENT PARK - Helida, Asvic; Susilawati, Oktavia; Syahroni, S.P, M.Si, Sasua Hustati; Azhar, Khorik (Universitas Muhammadiyah Palembang, 2023)
Birds need habitat conditions that are suitable and safe from all kinds of disturbances, which can be an important factor in the presence of birds in a place. The aim of this research is to analyze the diversity of bird species and the factors that influence the existence of bird species in the Sriwijaya Royal Archaeological Park, Palembang. The method used in this research is quantitative descriptive data taken using the